# If Sndenotes the sum of first n terms of A.P and S2n=3Sn then S3n/ Sn is equal to ?

1
by ZealMalik849

Log in to add a comment

by ZealMalik849

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

S_2n = 3 S_n

S_2n = (2a + (2n-1)d )* 2n/2

= (2a +(n-1)d) n + n^2 d

= 2 * S_n + n^2 d

as S_2n = 3 S_n, S_n = n^2 * d

S_3n / S_n = (3n)^2 d / (n^2 d) = 9

S_2n = (2a + (2n-1)d )* 2n/2

= (2a +(n-1)d) n + n^2 d

= 2 * S_n + n^2 d

as S_2n = 3 S_n, S_n = n^2 * d

S_3n / S_n = (3n)^2 d / (n^2 d) = 9